Customer Relationship Management, Service Delivery and Responsiveness: A supply chain Perspective for Customer’s Retention - Baharuddin Baharuddin; Syamsu Kamaruddin; Harifuddin Halim (International Journal of Supply Chain Management, 2019)
This study aims to analyze the supply chain perspective in terms of customer relationship management, delivery of services, and responsiveness with their impact on customer’s retention. For the analysis purpose, this study has collected primary data through questionnaire approach from a sample of 341 customers. Both descriptive and regression techniques are applied, and findings are presented with some significant discussion. It is observed that customer’s retention is positively influenced by the customer relationship management factors like passionate and friendly behavior of sales personnel, their courtesy and offering the comprehensive product’s introduction to the customers. Whereas, delivery of service in terms of high satisfaction to customers, quality based are positively influencing on customer’s retention. However, the effect of reliable, timely and flexible service delivery is negatively influencing on customer’s retention. In addition, more responsiveness in terms of time to inquiries and orders, and being timeliness to execute the order have shown their direct impact on customer’s retention.